Eco-friendly approaches to aquaculture wastewater treatment: Assessment of natural coagulants vis-a-vis chitosan. (September 2021) - Iber, Benedict Terkula; Okomoda, Victor Tosin; Rozaimah, Sheikh Abdullah; Kasan, Nor Azman
Abstract: Aquaculture intensification is providing cheap protein for the populace around the world. However, the rapid growth of aquaculture is resulting in the production of wastewater which could be harmful to the environment if discarded without treatment. The conventional methods of wastewater treatment involve the use of synthetic chemicals. Despite its effectiveness, concern over the environmental safety of their prolonged use has been raised. It is therefore imperative to identify natural, biodegradable, non-toxic, affordable, and efficient alternatives for wastewater treatment. This review examines the various components of aquaculture wastewater and the different eco-friendly approaches to its treatment which are viable alternatives to synthetic coagulants. Also, we examined herein the choice of chitosan over chitin in wastewater treatment; their coagulating and flocculating ability, and production procedures. The various advantages and drawbacks to mass utilization of natural coagulants were also advanced with a view on addressing the needed research interventions to achieving commercial usage. Graphical abstract: Unlabelled Image Highlights: Aquaculture wastewaters need to be treated before disposal. Chitosan is a promising natural, biodegradable and affordable biopolymer. Commercialization of biopolymers require more research to achieve.